2008
DOI: 10.1152/ajpcell.00076.2008
|View full text |Cite
|
Sign up to set email alerts
|

Alterations in mitochondrial function and cytosolic calcium induced by hyperglycemia are restored by mitochondrial transcription factor A in cardiomyocytes

Abstract: Mitochondrial transcription factor A (TFAM) is essential for mitochondrial DNA transcription and replication. TFAM transcriptional activity is decreased in diabetic cardiomyopathy; however, the functional implications are unknown. We hypothesized that a reduced TFAM activity may be responsible for some of the alterations caused by hyperglycemia. Therefore, we investigated the effect of TFAM overexpression on hyperglycemia-induced cytosolic calcium handling and mitochondrial abnormalities. Neonatal rat cardiomy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
43
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(48 citation statements)
references
References 43 publications
3
43
0
2
Order By: Relevance
“…2 F and G). It has previously been reported that high-glucose-treated cardiomyocytes show significant loss in complex IV activity (11,18). Our results directly implicate O-GlcNAcylation in the mechanism of this loss of complex IV activity.…”
Section: Mitochondrial Ogt Is Increased and Mislocalized In Diabetic Ratsupporting
confidence: 78%
See 1 more Smart Citation
“…2 F and G). It has previously been reported that high-glucose-treated cardiomyocytes show significant loss in complex IV activity (11,18). Our results directly implicate O-GlcNAcylation in the mechanism of this loss of complex IV activity.…”
Section: Mitochondrial Ogt Is Increased and Mislocalized In Diabetic Ratsupporting
confidence: 78%
“…Within the cardiovascular system, significant levels of O-GlcNAcylation have been observed on myofilament proteins, which severely affect contractile force generation (10). Alterations in cardiac O-GlcNAc levels significantly affect Ca 2+ handling and Serca2a function (11). STIM1 a modulator of cardiomyocyte calcium entry is modified by O-GlcNAc, which affects cellular calcium translocation (12).…”
mentioning
confidence: 99%
“…The HIGH COMBI blastocysts tended to display upregulated expression of MNSOD, an enzyme that plays a protectant role against oxidative stress (Harvey et al 1995), which might be the result of a compensatory mechanism in response to a shifted REDOX potential at earlier stages of development and in turn affect the activity of REDOX-sensitive transcription factors, a suggestion supported by our previous demonstration of SLC2A1 mRNA upregulation in HIGH COMBI embryos (Van Hoeck et al 2011). Moreover, the HIGH COMBI embryos showed higher expression of TFAM, which is essential in stabilizing mitochondrial DNA and for which overexpression is reported to be related to oxidative stress (Suarez et al 2008). Interestingly, a significant increase was also observed in the mRNA encoding enzymes involved in the fatty acid synthesis pathways; namely ACSL1 and ACCA in HIGH COMBI blastocysts.…”
Section: Discussionmentioning
confidence: 71%
“…Overexpression of both TFAM and TFB2M has been demonstrated to increase transcriptional activity 2-fold, while concurrently providing protection against stressinduced reductions in SERCA2a mRNA levels (Watanabe et al 2011). Furthermore, the expression of TFAM is downregulated in the diabetic heart and in conditions of cardiac failure postmyocardial infarction (Choi et al 2001;Ikeuchi et al 2005;Suarez et al 2008a). Thus, transcription factors including TFAM and TFB2M are essential in regulating the transcription of the ATP2a2 gene.…”
Section: The Atp2a2 Gene Encodes Serca2a Proteinmentioning
confidence: 99%